The Value of Continuous ST-Segment Monitoring in the Emergency Department. (October 2015) - Bovino, Leonie Rose; Funk, Marjorie; Pelter, Michele M.; Desai, Mayur M.; Jefferson, Vanessa; Andrews, Laura Kierol; Forte, Kenneth
Abstract : Practice standards for electrocardiographic monitoring recommend continuous ST-segment monitoring (C-STM) in patients presenting to the emergency department (ED) with signs and/or symptoms of acute coronary syndrome (ACS), but few studies have evaluated its use in the ED. We compared time to diagnosis and 30-day adverse events before and after implementation of C-STM. We also evaluated the diagnostic accuracy of C-STM in detecting ischemia and infarction. We prospectively studied 163 adults (preintervention: n = 78; intervention: n = 85) in a single ED and stratified them into low ( n = 51), intermediate ( n = 100), or high ( n = 12) risk using History, ECG, Age, Risk factors, and Troponin (HEART) scores. The principal investigator monitored participants, activating C-STM on bedside monitors in the intervention phase. We used likelihood ratios (LRs) as the measure of diagnostic accuracy. Overall, 9% of participants were diagnosed with ACS. Median time to diagnosis did not differ before and after implementation of C-STM (5.55 vs. 5.98 hr; p = 0.43). In risk-stratified analyses, no significant pre-/postdifference in time to diagnosis was found in low-, intermediate-, or high-risk participants. There was no difference in the rate of 30-day adverse events before versus after C-STM implementation (11.5% vs. 10.6%; p = 0.85). The +LR and −LR of C-STM for ischemia were 24.0 (95% confidence interval [CI]: 1.4, 412.0) and 0.3 (95% CI: 0.02, 2.9), respectively, and for infarction were 13.7 (95% CI: 1.7, 112.3) and 0.7 (95% CI: 0.3, 1.5), respectively. Use of C-STM did not provide added diagnostic benefit for patients with signs and/or symptoms of myocardial ischemia in the ED.